2013
DOI: 10.1093/aob/mct163
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two toxicities: malformed selenoproteins and oxidative stress both contribute to selenium stress in plants

Abstract: Malformed selenoproteins and oxidative stress are two distinct types of stress that drive selenium toxicity in plants and could impact cellular processes in plants that have yet to be thoroughly explored. Although challenging, deciphering whether the extent of selenium toxicity in plants is imparted by selenoproteins or oxidative stress could be helpful in the development of crops with fortified levels of selenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
179
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 60 publications
4
179
0
7
Order By: Relevance
“…4 Se accumulation in roots, stems, and leaves of tobacco plants under different levels of Se treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Se accumulation in roots, stems, and leaves of tobacco plants under different levels of Se treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies revealed that Se promotes the growth of ryegrass [3], tea [9], rice [10], and soybean [11]. However, excess Se accumulation (>0.1% plant DW) is generally toxic to plants, except for rare Se-hyperaccumulating plants [4].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Redox szenzitív elemként a szelén a környezet pH-jától és elektronaktivitástól függően 4 oxidációs állapotban lehet jelen a talajban. A szelénnek emberi és állati szervezetben, baktériumokban, valamint néhány zöld algában betöltött szerepe ma már jól ismert, de ez idáig nincs meggyőző bizonyíték a szelenoproteinek magasabb rendű növényekben való létét illetően (Van Hoewyk, 2013).…”
Section: Ii3 a Jelátviteli Molekulák éS Hormonok Kapcsolata A Szeléunclassified